MISCONCEPTION IDENTIFICATION USING THE CERTAINTY OF RESPONSE INDEX METHOD IN GAS KINETIC THEORY MATERIAL IN CLASS XI SENIOR HIGH SCHOOL - Nisa Siti Romadona; Wanda Siti Nur Aulia; Suci Rizki Lestari; Nana Nana (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2020)
This research aims to identify class XI MIPA1 senior high school students, who experience misconceptions on the kinetic theory of gas. The method used to determine students who experience misconceptions is the Certainty Response Index (IRK) method. This method has four indexes in identifying students' mastery of concepts, namely lucky guess (LG), not knowing concept (NKC/TTK), knowing concept (KC/TK), and misconception (M). The subjects of the study were senior high school students in class XI MIPA1 in Tasik Malaya. The research instrument used was a kinetic theory of gas test equipped with an IRK scale assessment instrument. This research is a quantitative descriptive research that can determine weaknesses in understanding students' physics concepts with the IRK method. The results of data analysis using IRK revealed that students who experienced lucky guess (LG) were 9.0%, students who knew the concept (TK) were 35.2%, students who lacked knowledge or did not know the concept (TTK) were 21.9%, and students experiencing misconceptions (M) of 33.8%. Based on the sub-topic analysis, the level of misconception the results are also in the high category. Thus it was concluded that through the IRK method it was identified that most students were still experiencing misconceptions, did not know the concepts, and were lucky guessed in understanding the kinetic theory of gas in the class XI MIPA1 of senior high school in Tasik Malaya.